Determination of some heavy metal concentrations in razor clam (Solen brevis) from Tanjung Lumpur Coastal waters, Pahang, Malaysia - Yunus, Kamaruzzaman; Md Suhaimi, Mohd Zahir; John, Akbar; Abdurahman, Siti Waznah; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin; Al-Barwani, Said Mohd; Goddard, J Stephen (Asian Network for Scientific Information, 2010)
An effort to analyze selected heavy metal accumulation by the razor clam (Solen brevis) from Tanjung Lumpur was conducted on January to April 2010. A total of fifty individuals of Razor clam Solen brevis were sampled and metals such as Iron (Fe), Zinc (Zn), Copper (Cu), Manganase (Mn), Lead (Pb) and Cadmium (Cd) Concentrations were determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Among the metals Fe occurred in elevated concentration in the soft tissue of razor clam followed by Zn. Cd was found to be in least concentration in the sample. Mean concentration of Fe, Zn, Mn, Cu, Cd and Pb in the soft tissue were 415.2±56.52, 87.74±11.85, 18.71±2.10, 8.64±1.75, 0.67±0.29 and 1.61±0.45 μg g-1 dw, respectively indicating that the bioaccumulation of essential metals in the soft tissue was greater than the non essential heavy metals. Metal accumulation in the soft tissue of razor clam followed Fe > Zn > Mn > Cu > Pb > Cd order in present study. The observed concentration of acute toxicity of metals in Solen brevis (Family: Solenidae) from Tanjung Lumpur Coastal waters was lower than the permissible limit recommended by National and international standards proved that this species could be utilized for human consumption.